(untitled) (Brazilian Dental Science, 2020)
Impact Factor (IF) means the scientometric index that represents the average annual number of citations that manuscripts published in a specific journal received in the last two or three years [1, 2]. It expresses the relative importance of the journal in the field from the view of scientific community. Different databases have their own impact factor calculation based on the citations in the indexed journals. For the journals that are indexed on Web of Science, they are ranked by JCR (Journal Scientific Report)/ISI (Institute for Science and Information) in JIF (Journal Impact Factor). For Scopus by SJR (Scimago Journal Rank-citescore)/SNIP (Source Normalized Impact per Paper); etc. Since we got Scopus indexation in 2017, BDS has been growing its CiteScore index from 0.3 to 1.0 in 2020 [3]. This bibliometric index shows a positive trend for BDS during the last years. Our team is focused on the future with a score higher than “1.0”. Furthermore, BDS improves its Editorial Board. Twenty-four section editors and 30 assistant editors are directly involved weekly with the process of the manuscripts submitted to the journal. Opportunities arising from the pandemic brought improvements in the speed of evaluation process, in the distribution of the steps, in the partnership, digital or remote meetings, and visibility of the journal. The communion of ideals among the team members led BDS to a high profile on social networks as Instagram, Facebook and LinkedIn. Our posts have been shared with researchers with great success. By 2021, authors and readers can expect issues with the highest quality in science, commitment to innovation, and dissemination. Welcome to BDS journal once again. References • Frankernberger, R., Van Meerbeek, B. JAD in the context of bibliometric data. JAD (2020), n5, p. 439. doi:10.3290/j.jad.a45410 • Fernandes V., Salviano LR. Indicadores JCR, SNIP, SJR e Google Scholar. http://portal.utfpr.edu.br/pesquisa-e-pos-graduacao/indicadores/indicadores-externos/indicadores-externos • CiteScoreTracker. Scopus. [Internet]. Access in: 16 Dec 2020. Avaiable at: https://www.scopus.com/sourceid/21100831445